Dysbiosis of gut and urinary microbiota in urolithiasis patients and post-surgical cases - Yuanyuan Jia; Meng Han; Haoyu Ge; Jie Qiao; Ruyan Chen; Chenyu Li; Cailin Liu; Lei Fang; Yanhao Shen; Saiqi Qi; Yuli Wang; Xiaobing Guo (Frontiers in Cellular and Infection Microbiology)
BackgroundResearch on the microbial roles in urolithiasis primarily focuses on the intestinal microbiota. This study analyzed urine and fecal samples from three cohorts: healthy controls (Control), patients with urinary stones (US), and postoperative patients (PS). We conducted 16S rRNA sequencing analysis to evaluate the variations in microbial communities among these groups during urinary stone production and therapy processes.ResultsIn fecal microbiota, alpha diversity was lower in the stone group versus the control group, with the postoperative group showing the lowest diversity. The β diversity analysis revealed some differences in the microbial community structure of individuals with different health conditions. LEfSe and Wilcoxon analyses were utilized to discover species that exhibited significant differences between groups. Enterobacteriaceae and Bacteroides are more abundant in patients with stones. The increased abundance of Lactobacillus, Lachnospiraceae, Rumenococcaceae, Faecalibacterium, and Prevotella is associated with a reduced risk of kidney stones.ConclusionsAlterations in urinary and intestinal microbiota may indicate urolithiasis status and treatment response. Future studies should explore microbiota modulation (e.g., probiotics) as an adjunctive strategy, while antibiotic stewardship is warranted to minimize microbiota disruption.